2012
DOI: 10.1111/j.1523-5378.2011.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Demographic Characteristics and Upper Gastrointestinal Endoscopy Findings in HIV‐Positive, Antiretroviral‐Treated Patients With and Without Helicobacter pylori Coinfection

Abstract: In the antiretroviral therapy era, HIV-H. pylori coinfection is associated with a greater incidence of duodenal ulcers and higher CD4 counts, higher BMI, less comorbidity, and less frequent use of macrolides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(53 reference statements)
3
7
0
Order By: Relevance
“…In accordance with published data (Nkuize et al, 2010; Marano, Smith & Bonanno, 1993; Fialho et al, 2011; Chiu et al, 2004; Mohamed et al, 2002; Olmos et al, 2004; Nkuize et al, 2012), we also demonstrated the highest CD4 cell counts in HIV/ H. pylori co-infected patients. Moreover, CD4 cell counts show a positive increasing trend simultaneous with ART evolution from pre-HAART to modern HAART.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with published data (Nkuize et al, 2010; Marano, Smith & Bonanno, 1993; Fialho et al, 2011; Chiu et al, 2004; Mohamed et al, 2002; Olmos et al, 2004; Nkuize et al, 2012), we also demonstrated the highest CD4 cell counts in HIV/ H. pylori co-infected patients. Moreover, CD4 cell counts show a positive increasing trend simultaneous with ART evolution from pre-HAART to modern HAART.…”
Section: Discussionsupporting
confidence: 93%
“…First, it is a retrospective case-control study. Second, various risk factors for H. pylori acquisition, such as exposure to antibiotics, as well as to proton-pump inhibitors (PPI) and H2 blocker therapies, along with hypochlorhydria, body mass index, particular habits, which have all been addressed by numerous studies before (Fialho et al, 2011; Chiu et al, 2004; Olmos et al, 2004; Nkuize et al, 2012), were not explored. Third, we have not sufficiently explored H. pylori acquisition in HIV negative cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of H . pylori infection among HIV-positive patients is variable, ranging from 10% to 76%, depending on the population studied and the geographic area [ 3 , 4 – 7 ]. In a recent study in our center, the prevalence of H .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in our center, the prevalence of H . pylori co-infection was 48/145 (33%) among symptomatic HIV-positive patients who underwent UGI endoscopy, and was more common in patients of Black African origin and in heterosexuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, it is a retrospective case-control study. Second, various risk factors for H. pylori acquisition, such as exposure to antibiotics, as well as to proton-pump inhibitors (PPI) and H2 blocker therapies, along with hypochlorhydria, body mass index, particular habits, which have all been addressed by numerous studies before (12,13,25,26), were not explored. Third, we have not sufficiently explored H. pylori acquisition in HIV negative cohorts.…”
Section: Study Limitationsmentioning
confidence: 99%